1998
DOI: 10.1007/pl00009736
|View full text |Cite
|
Sign up to set email alerts
|

Changes in radial tree growth for Picea abies, Larix decidua, Pinus cembra and Pinus uncinata near the alpine timberline since 1750

Abstract: Changes in radial growth of the four coniferous species growing in the French Alps near the upper treeline are investigated. Thirty-seven populations of Norway spruce [Picea abies (L.) Karst.], European larch (Larix decidua Mill.), Swiss stone pine (Pinus cembra L.) and mountain pine (Pinus uncinata Mill. ex Mirb.)were sampled by taking 1320 cores and analysing treering widths. Sites were chosen in various climatic conditions (macroclimate and aspect) and on two kinds of bedrock in order to take into account t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
86
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 26 publications
11
86
3
2
Order By: Relevance
“…they receive less light because of the canopy cover and face fiercer competition at the ground and root level. In fact, under similar conditions in the Val Varaita similar results emerged [40], while in other areas of the Alps, various authors [4,42,48] have found growth rate increases that affected all age classes. However accurately interpreting trends in tree ring series and cambial age-stratified data is neither simple nor unequivocal, especially since the data is subject to numerous methodological biases [27,40].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…they receive less light because of the canopy cover and face fiercer competition at the ground and root level. In fact, under similar conditions in the Val Varaita similar results emerged [40], while in other areas of the Alps, various authors [4,42,48] have found growth rate increases that affected all age classes. However accurately interpreting trends in tree ring series and cambial age-stratified data is neither simple nor unequivocal, especially since the data is subject to numerous methodological biases [27,40].…”
Section: Discussionsupporting
confidence: 56%
“…The growth of small trees (h < 3 m) at the treeline may respond differently to climate than taller trees [19,33] but, in the study area, the growth change has been observed in the same time in individuals of different height (0.5-3 m) and of different age (> 40 years of age range) representing the occurrence of an "event" more than a "trend" [50]. Besides microclimate associated with microsite could control growth during the early stages of tree development [32,48] but the study site has a very regular slope and morphology and microsite influence is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radial growth enhancement has been observed in many treelines being mostly attributed to warmer temperatures (Rolland et al 1998;Camarero and Gutiérrez 2004;Salzer et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the growth is a useful indicator to examine how climatic conditions affect regeneration of trees at the timberlines. Although many researchers investigated the effects of climatic conditions on the tree growth at the timberlines in North America and Europe (e.g., Kienast et al 1987;Rolland et al 1998;Szeicz & MacDonald 1995;Paulsen et al 2000;Carrer & Urbinati 2004), there are few studies reported in Japan. Increased knowledge of the climate-growth relationships at the timberlines is of great importance for understanding the effects of global warming on the tree regeneration at the timberlines, especially in Japan, where there are many high mountains.…”
Section: Introductionmentioning
confidence: 99%